Orthodontic retreatment with segmented arch technique in unilateral posterior crossbite - Soncco Quispe, Jennisse Katherine (2021)
The unilateral posterior crossbite is a type of malocclusion that is characterized by an arch deficiency, in which asymmetries in the upper or lower arch may occur. One of the approaches is the segmented arch technique, which allows us to predict the results, minimizing treatment time and improving patient comfort. This case report aims to describe the clinical management of a unilateral posterior crossbite orthodontic retreatment using the segmented arch technique, through the use of devices such as ATP, lingual arch, bite plane, ending with MEAW archwires. It concludes with the importance of a correct diagnosis and the choice of an adequate technique for the treatment of a unilateral posterior crossbite. This technique is an important tool that every orthodontist should consider to define their treatment plan and thus avoid side effects and prolonged treatment.